Radiosurgery for brain metastases and cerebral edema. Issue 3 (March 2015) - Gazit, Inbal; Har-Nof, Sagi; Cohen, Zvi R.; Zibly, Zion; Nissim, Uzi; Spiegelmann, Roberto
Abstract The objective of this study was to assess reduction in cerebral edema following linear accelerator radiosurgery (LINAC) as first line therapy for brain metastasis. We reviewed the medical records of all patients who underwent LINAC radiosurgery for brain metastasis at our institution during 2010–2012, and who had not previously undergone either surgery or whole brain radiotherapy. Data were analyzed for 55 brain metastases from 46 patients (24 males), mean age 59.9 years. During the 2 months following LINAC radiosurgery, the mean steroid dose decreased from 4.8 to 2.6 mg/day, the mean metastasis volume decreased from 3.79 ± 4.12 cc to 2.8 ± 4.48 cc (p = 0.001), and the mean edema volume decreased from 16.91 ± 30.15 cc to 12.85 ± 24.47 cc (p = 0.23). The 17 patients with reductions of more than 50% in brain edema volume had single metastases. Edema volume in the nine patients with two brain metastases remained stable in five patients (volume change <10%, 0–2 cc) and increased in four patients (by >10%, 2–14 cc). In a subanalysis of eight metastases with baseline edema volume greater than 40 cc, edema volume decreased from 77.27 ± 37.21 cc to 24.84 ± 35.6 cc (p = 0.034). Reductions in brain edema were greater in metastases for which non-small-cell lung carcinoma and breast cancers were the primary diseases. Overall, symptoms improved in most patients. No patients who were without symptoms or who had no signs of increased intracranial pressure at baseline developed signs of intracranial pressure following LINAC radiosurgery. In this series, LINAC stereotactic radiosurgery for metastatic brain lesions resulted in early reduction in brain edema volume in single metastasis patients and those with large edema volumes, and reduced the need for steroids.